DISTINCTIVE DIALECT CAUSED BY REGIONAL BORDERS ON ‘SRINAHAN’ SOCIETY AS JAVANESE SPEAKERS - Didit Kurniadi (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2020)
A dialect shows its culture. Many aspects can be found in a dialect. The distinctive dialects that are spread across Indonesia are very diverse and should be explored to be publicized. One of those can be found in Srinahan Society. The objectives of this study are to find out what aspects found in the distinctive dialect of Srinahan society and what factors influence them. The study was conducted using descriptive qualitative research. The aspects that can be found are phonological, lexical and morphological. The results of this study show that; (1) local villagers who used to be majority farmers (did not like transmigration) and some created their own words for certain vocabulary, (2) the boundary of the area, surrounded by a long and wide river that could maintain the purity of the local dialect from intruders/new comers. (3) Dutch influence. Srinahan which is located between the area of the users of the eastern dialect of Javanese and the western Javanese dialect result in some distinctive linguistics aspects. The distinctive dialect that is used by Srinahan society is portraits of word variations that arise by the speakers, its local philosophy and its culture.